Trypanocidal activity of South American Vernonieae (Asteraceae) extracts and its sesquiterpene lactones. Issue 23 (2nd December 2021) - Sosa, Andrea; Salamanca Capusiri, Efraín; Amaya, Susana; Bardón, Alicia; Giménez-Turba, Alberto; Vera, Nancy; Borkosky, Susana
Abstract: Chagas disease is caused by Trypanosoma cruzi and affects the poorest population in the Americas. Fourteen plant extracts and seventeen sesquiterpene lactones from the tribe Vernonieae (Asteraceae), were evaluated for the first time against T. cruzi . Cytotoxicity employing HeLa cells was also assessed. The best results were obtained with leaves and flowers rinse extracts from Vernonanthura nebularum (E-1 and E-3) and Elephantopus mollis (E-11 and E-13), with IC50 values <2 µg/mL, being E-1 the most active (IC50 = 0.8 µg/mL). Additionally, these extracts displayed a good selectivity (SI > 10). The most active sesquiterpene lactones, isolated from the extracts, were 2 (2- methoxy-2, 5-epoxy-8-methacryloxygermacra-3Z, 11(13)-dien-6, 12-olide) and 6 (2- ethoxy-2, 5-epoxy-8-angeloxygermacra-3Z, 11(13)-dien-6, 12-olide) from V. nebularum and 12 (8α-methacryloxyhirsutinolide 13-O-acetate) from V. pinguis, with IC50 of 1.5, 2.1 and 2.0 µM, respectively. These compounds showed SI values >14, better than those of the reference drug nifurtimox. Plants living in South American ecosystems could become a potential source of trypanocidal agents. Graphical Abstract: